Conflict archaeology, historical memory, and the experience of war : beyond the battlefield - Tveskov, Mark Axel; Tveskov, Mark Axel; Bissonnette, Ashley Ann; Bissonnette, Ashley Ann (Cultural heritage studies, 2023)
Presents approaches to the archaeology of war that move beyond the forensic analysis of battlefields, fortifications, and other sites of conflict to consider the historical memory, commemoration, and social experience of war